A vision for actionable science in a pandemic (Nature Portfolio, 2020)
Cornelia Betsch (a psychologist, University of Erfurt), Vittoria Colizza (a computational epidemiologist, INSERM), Sara del Valle (a computational epidemiologist, Los Alamos National Laboratory), Chikwe Ihekweazu (a public health epidemiologist, Nigeria Centre for Disease Control) and Carmela Troncoso (a data security specialist, EPFL) talked to Nature Communications about their experience with COVID-19 response and their vision on a new system for disease surveillance and control, providing a view on how this should interact with policy making.